STUDI EMPIRIS SERVICESCAPE TERHADAP KEPUASAN KONSUMEN KAFE SUN OSING BANYUWANGI DI MASA PANDEMI COVID 19 - Habibi, Fawwaz Ahmad; Sumowo, Seno; Murtaliningtyas, Wenny (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to help sun osing cafes to survive in the long term by using a servicescape marketing strategy which includes Ambient Dimension, Design Dimension and Social Dimension. In this study using quantitative methods, purposive sampling technique involving 95 respondents. The results of multiple regression testing on the influence of the Ambient Dimension on consumers showed a significant positive effect. This proves that a good Ambient Dimension will increase the Consumers of Sun Osing Cafe Banyuwangi. The results of multiple regression testing on the influence of the De- sign Dimension on consumers show a significant positive effect. This proves that a quality Design Dimension will increase the Consumers of Sun Osing Cafe Banyuwangi. The results of multiple regression testing on the influence of Social Dimensions show that the effect on consumers is significantly positive. This proves that a high Social Dimension will increase the purpose of the Sun Osing Cafe Banyuwangi.